Teachers’ Stress and Wellbeing in North Macedonia: A Scoping Review - Demiri – Shaipi, Urime; Bajrami – Ollogu, Elisabeta; Xhelili, Arta (South Eastern European Journal of Public Health, 2024)
This scoping review aimed to analyze peer-reviewed studies on teachers’ work stress and wellbeing status in North Macedonia, addressing the stress prevalence among teachers and identifying gaps for future research. A database search was conducted in PubMed, Google Scholar, and EBSCO, and Google.com in English, Macedonian and Albanian Languages from 2010 to December 2023. The search yielded 631 articles, of which 11 were screened for eligibility, and six met the inclusion criteria. Four studies focused on work stress, two on burnout; however, none addressed teachers’ wellbeing, leaving this aspect unknown. The stress level among teachers was moderate to high, attributed to various work stressors and demographic factors. The findings highlight the need for more research on wellbeing and other aspects of mental health among teachers. Additionally, to support teacher wellbeing, the review suggests the substantial need for health promotion programs at both individual and institutional levels